2020
DOI: 10.1021/acssensors.9b02204
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-Modulated Downconversion Nanoparticles as Label-Free Biological Sensors

Abstract: Ultrasensitive detection of proteins and biomolecules has been previously achieved by optical nanoparticles (NPs) using the principles of Förster resonance energy transfer (FRET). However, the inherent need for labeling the target analyte in these assays hinders their applicability in point-of-use (POU) diagnostics. In this work, a label-free NP-based sensor has been developed that utilizes downconversion luminescence and surface electric dipoles as a novel approach for the detection of avidin. The long-lived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The integration of nanoscience with biomedicine has resulted in numerous technological advances in molecular sensing, targeted delivery, in vivo imaging, and gene therapy. For these applications, nanoparticles (NPs) are the fundamental units that provide the necessary biological response and functionality. , When NPs are introduced in in vivo environments, proteins from biological fluids instantaneously bind to the NP surface, leading to the formation of a shell known as the “protein corona” . Thus, any further interaction of NPs with biomolecules is mediated by the protein corona. , While most of the current studies focus on the biological activity of the protein within the corona, the mechanism of its formation and local orientation of proteins within the corona remain poorly understood. , This lack of understanding of protein corona characteristics is due to anisotropic shape and nonuniform distribution of chemical functional groups on the surface of protein molecules forming the corona. , To develop the next generation of functional nanomaterials for biomedical applications, it is critical to understand the local interactions driving the formation of the protein corona and thermodynamic state of the protein on the NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of nanoscience with biomedicine has resulted in numerous technological advances in molecular sensing, targeted delivery, in vivo imaging, and gene therapy. For these applications, nanoparticles (NPs) are the fundamental units that provide the necessary biological response and functionality. , When NPs are introduced in in vivo environments, proteins from biological fluids instantaneously bind to the NP surface, leading to the formation of a shell known as the “protein corona” . Thus, any further interaction of NPs with biomolecules is mediated by the protein corona. , While most of the current studies focus on the biological activity of the protein within the corona, the mechanism of its formation and local orientation of proteins within the corona remain poorly understood. , This lack of understanding of protein corona characteristics is due to anisotropic shape and nonuniform distribution of chemical functional groups on the surface of protein molecules forming the corona. , To develop the next generation of functional nanomaterials for biomedical applications, it is critical to understand the local interactions driving the formation of the protein corona and thermodynamic state of the protein on the NPs.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that the dipole moment of the biotin molecule is attracted to the negative surface of the SiN membrane and could slightly modify the PEG structure. Indeed, Bajgiran et al (Bajgiran et al, 2020) demonstrated that a biotinylated nanoparticle generates a positive dipole moment and could be used to detect avidin particles. Similarly, a decrease of the apparent thickness was observed when the streptavidin molecules were added (h PEG > h Biotin > h' Streptavidin ).…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide-based downconversion probes possess good characteristics for optical imaging, such as narrow emission bandwidths, large Stokes shifts, and good photostability [40,41]. They are usually synthesized by doping Tb 3+ , Eu 3+ , and Dy 3+ to achieve the traditional Stokes luminescence, and they are activated by UV light to generate visible-NIR emission [42].…”
Section: Lanthanide-based Downconversion Probesmentioning
confidence: 99%